Analysis of efficiency of application of media with hyaluronic acid in cryoprotocols - Natalia V. Protopopova; Elena B. Druzhinina; Kseniia V. Krylova; Iuliia V. Mylnikova; Jan A. Dvoryanov; Albina V. Labygina; Inna I. Kovalenko (Гинекология, 2020)
According to the World Health Organization, about 2 million new couples experience infertility annually, and their number is growing. An effective way to overcome infertility is assisted reproductive technology (ART). Cryopreservation will rationally solve the issue of preservation and further use of embryos: to delay pregnancy for some time considering womans desire and to prevent ovarian hyperstimulation syndrome. Embryo freezing allows to reduce the rate of repeated ovarian stimulation and perform preimplantation genetic diagnosis. Over the past decades, various cryotransfer options have been proposed to increase ART treatment efficacy, including the use of a culture medium with a high concentration of hyaluronic acid, but there are conflicting data on the use of such a medium in ART programs.